Secular variations in sperm quality: fact or science fiction? - Luc Multigner; Alejandro Oliva
The debate concerning the possible degradation in human sperm quality began in the 1970s, was revived at the beginning of the 1990s and has continued to mobilize the scientific community ever since. After the meta-analysis by Carlsen et al. (1992) showing a decline in human semen quality over the last 50 years, several groups investigated the sperm characteristics of more or less homogeneous groups of men who had provided semen at the same center for 10 to 20 years. A significant decrease in sperm concentration was reported in some studies, but not in others. Meanwhile, there is an increasing number of reports suggesting that physical and chemical factors introduced and spread by human activity in the environment may have contributed to sperm decline. At the end of the 20th century the debate on declining semen quality is not closed. The lack of certainty and the serious consequences that such a decline would have on the fertility of human populations make this an important public health issue at the start of the 21st century. For this reason, intensive research should be developed in both fundamental and epidemiological domains, particularly in South America, where industrial and agricultural pollution pose a serious threat to the population.